2017
DOI: 10.1002/btpr.2411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper variation in yeast hydrolysate on C‐terminal lysine levels of a monoclonal antibody

Abstract: The ability to control charge heterogeneity in monoclonal antibodies is important to demonstrate product quality comparability and consistency. This article addresses the control of C-terminal lysine processing through copper supplementation to yeast hydrolysate powder, a raw material used in the cell culture process. Large-scale production of a murine cell line exhibited variation in the C-terminal lysine levels of the monoclonal antibody. Analysis of process data showed that this variation correlated well wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In the previously published work where increased Cu in the bioreactor lead to increased C-terminal lysine, increased lactate consumption was also observed (Mitchelson et al, 2017). In our case, we did not observe a significant change in lactate consumption across conditions (Figure 2c) despite very different amounts of Cu added to the bioreactor (Figure 3d).…”
Section: Redox Control Prevents Mab Reduction Without Affecting Othsupporting
confidence: 77%
See 1 more Smart Citation
“…In the previously published work where increased Cu in the bioreactor lead to increased C-terminal lysine, increased lactate consumption was also observed (Mitchelson et al, 2017). In our case, we did not observe a significant change in lactate consumption across conditions (Figure 2c) despite very different amounts of Cu added to the bioreactor (Figure 3d).…”
Section: Redox Control Prevents Mab Reduction Without Affecting Othsupporting
confidence: 77%
“…Increased Cu in the bioreactor has been previously demonstrated to increase the amount of C‐terminal lysine present on a mAb (Mitchelson, Mondia, & Hughes, 2017). We thus quantified the percent C‐terminal lysine.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4, increasing copper concentrations gave an increasing titer trend with decreased lactate production. Although not shown here, increased copper concentrations can also lead to increased oxidative culture stress and, through the action of the copper essential cofactor peptidylglycine α‐amidating mono‐oxygenase, an increase in basic protein isoforms 9,14 . To mitigate the risk of these two negative effects and to saturate the impact of potential impurity shifts, intermediate basal and feed copper concentrations were chosen for future development work.…”
Section: Resultsmentioning
confidence: 99%
“…Raw material variability in cell culture media has been shown to cause an abundance of problems which can affect a wide range of cell culture characteristics including cell growth, product quality, and drug efficacy. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] There are multiple sources for raw material nonuniformity including material misformulation, impurities and contaminants, and chemical degradation. 5 The most common impurities are trace elements from numerous raw material sources.…”
Section: Introductionmentioning
confidence: 99%
“…Today, there exists an entire industry centered around the formulation of cell culture media to suit specific cell lines (Jayme et al, 1997) and medium development is a major topic of study under the cell culture umbrella (Ritacco et al, 2018) as it has been demonstrated that improvements in medium formulation (and the subsequent optimization of the process feed strategy) can result in higher productivity and lower cost of goods in protein manufacturing processes (Hakkinen et al, 2018; Y. M. Huang et al, 2010; Xu et al, 2017). A prominent topic in the development of media is the availability of trace metals, such as copper, iron, and manganese, which are critical to maintain product titer and quality (Ehret et al, 2019; Mitchelson et al, 2017; Vijayasankaran et al, 2013).…”
Section: Introductionmentioning
confidence: 99%